2013
DOI: 10.5966/sctm.2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing In Vivo Survival of Adipose-Derived Stromal Cells Through Bcl-2 Overexpression Using a Minicircle Vector

Abstract: Tissue regeneration using progenitor cell-based therapy has the potential to aid in the healing of a diverse range of pathologies, ranging from short-gut syndrome to spinal cord lesions. However, there are numerous hurdles to be overcome prior to the widespread application of these cells in the clinical setting. One of the primary barriers to effective stem cell therapy is the hostile environment that progenitor cells encounter in the clinical injury wound setting. In order to promote cellular survival, stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…It is speculated that the difference of transfection efficiency originates from a different MSC source (hUC vs hAT and hBM); in our experiments, the hAT-and hBM-MSCs also showed different transfection efficiencies. On the other hand, Hyun et al used nucleofection technology, instead of the cationic liposome method, and obtained 25e35% transfection efficiency in hAT-MSCs [18]. Compared with these efficiencies, we achieved much higher transfection efficiency (up to 63e66%) in hAT-and hBM-MSCs using microporation, a newly developed electroporation technology.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is speculated that the difference of transfection efficiency originates from a different MSC source (hUC vs hAT and hBM); in our experiments, the hAT-and hBM-MSCs also showed different transfection efficiencies. On the other hand, Hyun et al used nucleofection technology, instead of the cationic liposome method, and obtained 25e35% transfection efficiency in hAT-MSCs [18]. Compared with these efficiencies, we achieved much higher transfection efficiency (up to 63e66%) in hAT-and hBM-MSCs using microporation, a newly developed electroporation technology.…”
Section: Discussionmentioning
confidence: 86%
“…In the case of minicircle, the cationic liposome method also seemed to be also inefficient although it showed higher transfection efficiency compared with only plasmid. Until now, minicircles have been employed for transgene expression in MSCs in two reported studies [18,19]. Daneshvar et al transfected human umbilical cord (hUC)-MSCs with minicircles, which generated 18% GFP þ MSCs [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, prior studies have shown that Bcl-2 can be used to enhance stem cell survival following transplantation into calvarial defects and stented fullthickness skin wounds. 22 Osteoblasts may represent an ideal target for such an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Human B-cell Leukemia/lymphoma2 (Bcl-2) and Human 8-Hydroxy-deoxyguanosine (8-OHdG) levels were determined quantitatively exactly as described by Hyun et al (2013) and Sova et al (2010) respectively. The kits supplied by Glory Science Co., Ltd. cat n. TX 78840, USA.…”
Section: Sample Collection and Biochemical Analysismentioning
confidence: 99%